2004
DOI: 10.1002/ab.20081
|View full text |Cite
|
Sign up to set email alerts
|

Criminal attitudes to violence: Development and preliminary validation of a scale for male prisoners

Abstract: Two studies report on the development and preliminary psychometric properties of a new scale measuring criminal attitudes to violence. In Study 1, the responses of a mixed sample of male prisoners were used to select 20 scale items from a larger pool. The final scale (the Criminal Attitudes to Violence Scale; CAVS) was designed so that it had a single-factor structure and was uncorrelated with a measure of social desirability bias. It demonstrated high internal reliability, and a strong relationship to a self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 38 publications
(47 reference statements)
6
73
0
1
Order By: Relevance
“…Another potential explanation for the inverse relationship among the high criminal intent group could be a proactive, reactive difference among this high group Walters, 2009). The association between criminal intent group membership and only one offence type -violent offending -is consistent with the suggestion that criminogenic cognitions may not be engaged in equally by different offender groups (Polaschek et al, 2004;Wilson et al, 2003). The reason for the negative association between violent offenses and membership in the 'High criminal intent' group is, however, unclear.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Another potential explanation for the inverse relationship among the high criminal intent group could be a proactive, reactive difference among this high group Walters, 2009). The association between criminal intent group membership and only one offence type -violent offending -is consistent with the suggestion that criminogenic cognitions may not be engaged in equally by different offender groups (Polaschek et al, 2004;Wilson et al, 2003). The reason for the negative association between violent offenses and membership in the 'High criminal intent' group is, however, unclear.…”
Section: Discussionsupporting
confidence: 54%
“…Although certain thinking styles promote criminal behaviour, these criminogenic cognitions may not be engaged in equally by different offender groups (Polaschek, Collie & Walkey, 2004;Wilson, Attrill & Nugent, 2003). Sex offenders and white-collar criminals are two groups of offenders that typically score lower than other offenders on criminal thinking scales (Hatch-Maillette, Scalora, Huss & Baumgartner, 2001;.…”
Section: Criminal Intent and Offence Typementioning
confidence: 99%
“…Consistent with the findings of the present study, the ad hoc per protocol analysis of Cullen et al"s [18] 12-month follow-up data found a treatment effect for violent attitudes. Thus "softer" measures evaluating antisocial attitudes are likely to be important early markers due to their association with offending [41][42][43][44]. Thus antisocial attitudes and behaviors, together with reconviction rates, should be the primary benchmarks for evaluating OBPs in MDOs.…”
Section: Discussionmentioning
confidence: 99%
“…Calculations performed at 80% power with an alpha level of 0.05 suggested that 35 participants per group were needed to detect a difference in the primary outcome measure of violent attitudes using the Total MVQ score with an effect size of . 42 …”
Section: Power Calculationmentioning
confidence: 99%
“…Attitudes during treatment, core beliefs associated with the offending behaviour, and empathy are identified as significant factors in considering the risk of recidivism of violent offenders, with negative attitudes and poor engagement in treatment linked to increased recidivism (Andrews & Bonta, 2006;Polaschek, Collie, & Walkey, 2004). Deficits in social perception and empathy, as well as cognitive distortions have been highlighted as pertinent factors in risk assessment of sex offenders (Blake & Gannon, 2010).…”
Section: Offence-related Cognitionmentioning
confidence: 99%